Pulmonary Alveolar Proteinosis - Wang, Tisha; Lazar, Catherine A.; Fishbein, Michael C.; Lynch, Joseph P., III (Seminars in Respiratory and Critical Care Medicine, 2012)
Pulmonary alveolar proteinosis (PAP) is a rare disorder characterized by the accumulation of surfactant lipids and protein in the alveolar spaces, with resultant impairment in gas exchange. The clinical course can be variable, ranging from spontaneous resolution to respiratory failure and death. PAP in all forms is caused by excessive accumulation of surfactant within the alveolar spaces. Autoimmune PAP accounts for the vast majority of cases in humans and is caused by autoantibodies to granulocyte-macrophage colony-stimulating factor (GM-CSF), which results in impaired catabolism and clearance of surfactant lipids and proteins. Inherited or congenital forms of PAP are exceptionally rare and caused by mutations of genes encoding for surfactant proteins. Secondary forms of PAP are associated with diverse clinical disorders and are caused by reduced alveolar macrophage numbers or function with resultant reduced pulmonary clearance of surfactant. PAP is characterized by progressive exertional dyspnea and nonproductive cough with hypoxemia. Bilateral infiltrates are typically present on chest radiograph, and high-resolution computed tomography reveals diffuse ground-glass opacities and airspace consolidation with interlobular septal thickening in a characteristic “crazy paving” pattern. Although surgical lung biopsy will provide a definitive diagnosis, a combination of typical clinical and imaging features with periodic acid-Schiff (PAS)-positive material on bronchoalveolar lavage and transbronchial biopsies is usually sufficient. The standard of care for treatment of PAP remains whole lung lavage, but treatment is not required in all patients. Autoimmune PAP has also been successfully treated with GM-CSF, both inhaled and systemic, but the optimal dose, duration, and route of administration of GM-CSF have not been elucidated.
Keywords: pulmonary alveolar proteinosis (PAP); surfactant; granulocyte-macrophage colony-stimulating factor (GM-CSF); crazy-paving; autoantibodies; whole lung lavage; autoimmune disease